Effect of chelated mineral supplementation on productive and reproductive performance of lactating buffalo - KANTWA, S C; SHEKHAWAT, S S; PRATAP, RAM; MEENA, YOGENDRA K; SAMOTA, S D (The Indian Journal of Animal Sciences, 2022)
The present study was conducted to assess the effect of chelated mineral mixture supplementation on the productive, reproductive performance and economics of lactating buffalo. Trial was conducted on 40 buffaloes of nearly at the same lactation stage, milk yield and parity selected from village- Bhakhrana, Block- Kotputli, District- Jaipur, Rajasthan. Buffaloes were divided in two groups; 20 buffaloes were kept in each group, viz. control and treatment group. Two buffaloes of each farmer were selected to maintain similarity in feeding and management practice. Treatment group was fed with chelated mineral mixture @ 40 g/buffalo/day till 90 days of early lactation period, whereas the control group was not supplemented. The data were recorded by the farmers daily in the morning and evening and by the researcher at fortnightly interval. Analysis of data revealed that supplementation of chelated mineral mixture increased the milk yield by 1.55 lit/day (15.82%) in treated group. Similarly, reproductive performance traits such as onset of first estrum after calving, no. of AI required for conception and service period were also recorded at the same interval between these groups. The B:C ratio of chelated mineral mixture supplementation was observed 1:7.75 under farmer management practices. These findings may suggest that supplementation of chelated mineral mixture enhanced the productive and reproductive performance for getting higher return and sustainable profit from buffalo farming.